APPLICATION OF TERRESTRIAL LASER SCANNING (LIDAR) IN ROCK SLOPE STABILITY. ΑΝ ΕXAMPLE FROM NORTHERN GREECE - Ampatzi, G.; Chatzigogos, N.; Makedon, M.; Papathanassiou, G.; Marinos, V. (Bulletin of the Geological Society of Greece, 2016)
The scope of this study is to investigate the failure mechanisms of the eastern coastal zone of Mount Athos, using the LiDar device for the 3D mapping of the structural features of the rock mass. Therefore emphasis was given to the study of the planes of discontinuities that can trigger potential failures. All slopes were scanned by LiDar device in order to capture their structure and especially the orientation and the spacing of the discontinuities. The data were processed in order to produce the microtectonic model of the slopes and evaluate the potential slope failures. Finally some remedial measures are proposed.The results and the reliability as well as the constrictions of the applied methodology are discussed for future applications.